Cytotaxonomic considerations with the description of two new NOR locations for South American toads, genus Bufo (Anura: Bufonidae) - Baldissera Jr., Flavio A. [UNESP]; Batistic, Radenka F.; Haddad, Célio F.B. [UNESP] (My University, 1999)
Cytogenetic studies were made on Brazilian Bufo: B. marinus, B. paracnemis, B. ictericus, B. rufus, B. arenarum, B. crucifer, Bufo granulosus, B. pygmaeus and B. margaritifer (= B. typhonius). All these species had a typical karyotype of 2n = 22. Species from the marinus and crucifer groups had NORs on Chromosome 7, species from the granulosus group had NORs on Chromosome 5, and B. margaritifer had NORs on Chromosome 10. The last two locations of NORs are described for the first time for the genus Bufo in South America.